Isolation and Identification of Potential Antineoplastic Bioactive Phenolic Compounds in Malaysian Honeys - Norjihada Izzah Ismail, Mohammed Rafiq Abdul Kadir, Razauden Mohamed Zulkifli (Journal of Applied Pharmaceutical Science, 2015)
The role of honeys as chemopreventive agents was inferred from their phenolic composition. The present study aims to isolate and identify such phenolic compounds with anticarcinogenic potential from the sugar matrix of Malaysian honeys. Phenolic compounds in Malaysian Acacia, Gelam and Tualang honey samples were isolated using octadecyl (C18) silica solid phase extraction (SPE) technique and identification was performed using high-performance liquid chromatography (HPLC) with diode array detector (DAD). Identification of phenolic compounds was achieved by comparing chromatographic retention times of honey samples with those of authentic standard compounds. HPLC analysis confirmed the presence of anticancer phenolic compounds in all honey samples with considerable variation observed among both different and the same types of honey. Six flavonoids (quercetin, naringenin, kaempferol, rutin, hesperetin, and apigenin), two phenolic acids (p-coumaric acid, and ferulic acid) and two tannins (ellagic acid, and penta-O-galloyl-β-D-glucose [PGG]) were the bioactive anticancer compounds identified. The presence of PGG in Malaysian honey was described for the first time. This study concludes that these three types of Malaysian honey possessed anticancer properties at varying degrees. Their potential usage as natural anticancer therapeutic agents with numerous health benefits could be further explored and considered as an alternative for current anticancer drugs.
Keywords: Honey, flavonoids, phenolic acids, tannins, anticancer, high-performance liquid chromatography (HPLC).